TECHNOLOGICAL FEATURES OF BECKERS BRAND PAINT PRODUCTS - OLIJNYK, Halina (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The work presents the results of research related to the use of paint and varnish products of the “BESKERS” brand in a modern interior. The technological characteristics of the products were studied. Specific features of product application are determined. Today, paint and varnish products of the “BECKERS” brand are a leading trade and retail network that offers high-quality imported varnishes, paints and other paint and varnish materials. Turning to the “BECKERS” brand, you can get high-quality products, which today are presented in a fairly wide range. These are varnishes, paints, antiseptics, primers, putties for finishing all types of internal and external surfaces. The full range of products includes varnishes, paints and other paint and varnish materials of more than four thousand items. The offered varnishes and paints satisfy the most demanding taste. You can not only choose suitable varnishes or paints, but also get technical assistance on how to correctly apply and combine varnishes, paints and other paint and varnish materials. The “BECKERS” trademark has a comprehensive approach to the formation of an assortment policy. Therefore, the trade network offers not only varnishes and paints, but also related materials, such as painting tool ANZA (Anza, Sweden), abrasive materials KA.ER (KA.EF, Germany), personal protective equipment MSA-Auer (МСА-Auer, USA). With the help of “BECKERS” paint and varnish products, you can professionally paint a wooden house and give it an aesthetic appeal and protect it from various external adverse environmental factors. The “BECKERS” brand offers the most modern varnishes, paints and other paint and varnish materials and technologies in the most optimal ratio of price and quality and maximally meet modern demands and key trends in woodworking. The use of “Beckers” brand products in a modern interior requires compliance with a special material application technology, use of special equipment, etc. Those who want to keep up with the times should pay attention to the most modern European materials for furnishing interiors. An example of such an application is the products of the “Beckers” trademark. It does not contain toxic impurities and can be used for processing almost any premises. VAGTLAZUR decorative paint creates a unique visual sensation of velvet fabric. The paint has pastel-sand halftones and is produced in a wide variety of colors and shades. VAGTLAZUR provides impeccable reliability, high impact and scratch resistance, adds uniqueness, refinement and elegance to the interior.